How does ownership structure affect the profitability of Turkish banks? A comparative analysis of determinants (Public Sector Economics - submission site, 2024)
This study examines the determinants of profitability of deposit banks in Turkiye taking into account differences in the ownership structures of public, private domestic and foreign-owned banks. The aim of the study is to analyse whether the factors determining profitability change depending on the managerial differences that the ownership structure may entail. A seemingly unrelated regression method with monthly data from 2010 to 2022 is used for this purpose. Our findings suggest that the real effective exchange rate, inflation, and non-interest income variables have common effects on profitability regardless of bank ownership. However, the bank capital ratio, bank size, loan to deposit ratio, and economic activity affect profitability differently across bank ownership types.